Prevalence and determinants of depression, anxiety and stress among psychiatric nurses in Ghana: a cross-sectional study - Sampson Opoku Agyemang; Jerry Paul Ninnoni; Nancy Innocentia Ebu Enyan (BMC, 2022)
Abstract Background The job demand and stress associated with the nursing profession expose nurses to an increased risk of psychiatric morbidities such as anxiety and depression. This study assessed the prevalence of depression, anxiety and stress among psychiatric nurses in Ghana. Methods A cross-sectional survey was conducted in three psychiatric hospitals in Ghana between March 2020 and May 2021. Simple random sampling technique were used to select 311 psychiatric nurses. Beck's Depression Inventory, Beck's Anxiety Inventory and Perceived Stress Scale were used to assess depression, anxiety and stress, respectively. Data were analysed using SPSS version 23.0. Results The results showed that 19.6% of psychiatric nurses experienced mild to severe depression, 27% mild to severe anxiety and 42% mild to high stress. Regression analysis showed that participants with a diploma qualification had higher odds of having moderate depression compared to those with a master's degree. In terms of stress, participants with a diploma qualification were 29.6% less likely to have moderate stress compared to those with a master's degree. Those with a bachelor's degree were 7.1% less likely to have moderate stress compared to those with a master's degree. Conclusion Psychiatric nurses experience depression, anxiety and stress to varying degrees. Education level was identified as a determinant of depression, anxiety and stress. Therefore, preventive strategies should be designed to reduce the risk of these conditions.